2015
DOI: 10.5194/angeo-33-471-2015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the enhanced negative correlation between electron density and electron temperature related to earthquakes

Abstract: Abstract. Ionospheric perturbations in plasma parameters have been observed before large earthquakes, but the correlation between different parameters has been less studied in previous research. The present study is focused on the relationship between electron density (N e ) and temperature (T e ) observed by the DEMETER (Detection of Electro-Magnetic Emissions Transmitted from Earthquake Regions) satellite during local nighttime, in which a positive correlation has been revealed near the equator and a weak co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Once all these plasma parameters were perturbed at the same time, N e ‐ T e and N i ‐ T i generally presented positive correlations during ionospheric heating, while N i (H + ) and N i (He + ) exhibited negative variations with N i (O + ). This positive correlation in density and temperature is quite different to those enhanced negative N e ‐ T e correlations related to seismic activity [ Shen et al , ], which illustrates the different interaction processes between HF‐induced and earthquake‐related ionospheric perturbations. Vartanyan et al [] simulated the variation of N i (O + ) for different T e pumping rates modifying the SAMI2 model, and their results showed a positive correlation between these two parameters, with a larger‐amplitude N i (O + ) variation under a higher heating rate.…”
Section: Discussionmentioning
confidence: 89%
“…Once all these plasma parameters were perturbed at the same time, N e ‐ T e and N i ‐ T i generally presented positive correlations during ionospheric heating, while N i (H + ) and N i (He + ) exhibited negative variations with N i (O + ). This positive correlation in density and temperature is quite different to those enhanced negative N e ‐ T e correlations related to seismic activity [ Shen et al , ], which illustrates the different interaction processes between HF‐induced and earthquake‐related ionospheric perturbations. Vartanyan et al [] simulated the variation of N i (O + ) for different T e pumping rates modifying the SAMI2 model, and their results showed a positive correlation between these two parameters, with a larger‐amplitude N i (O + ) variation under a higher heating rate.…”
Section: Discussionmentioning
confidence: 89%
“…Louerguioui et al [14] reported that the anomalous changes in the computed ULF electric component along the direction of the Z-axis were obviously detected on the 1st, 11th, and 17th days before the earthquake. In addition to the above earthquakes, many studies' results confirm that the DEMETER ionospheric perturbations are useful and sensitive for detecting anomalies related to earthquakes, such as the 2007 Pu'er earthquake [15][16][17], the L'Aquila earthquake [18,19], the Haiti earthquake [20], and so on.…”
Section: Introductionmentioning
confidence: 90%
“…The ionospheric plasma density (Ne and Ni) as precursory indicators of earthquakes have been main focus of majority of studies. The statistical analyses of ionospheric temperatures (Te and Ti) are comparatively less rich (Shen et al, 2015). increases as an effect of seismic activity (for example Oyama et al, 2016;Ho et al, 2013;Sarkar et al, 2012).…”
Section: Variation Of O + Ion Density During Earthquakesmentioning
confidence: 99%